Annual report 2016: CGIAR Research Program on Roots, Tubers and Bananas - CGIAR Research Program on Roots, Tubers and Bananas (CGIAR Research Program on Roots, Tubers and Bananas, 2017)
CGIAR Research Program on Roots, Tubers and Bananas 2016 Annual Report.